Hostel (Eli Roth, 2005 et 2007), le torture-porn et le cinéma d’exploitation : l’être humain à l’ère de sa reproductibilité technique - Pierre Jailloux (Transatlantica)
Produced by Quentin Tarantino, the first two installments of Hostel (Eli Roth, 2005, 2007) belong to a subgenre of horror that emerged in the early 2000s, the torture porn, and are heavily influenced by exploitation films. The system depicted in Hostel (you pay to torture and kill someone) is at the basis of a deliberate critique of a globalized contemporary world governed by rampant economic liberalism according to which anything or anyone can be bought or sold. The recycling of exploitation cinema conventions is more than just playful: it overlaps with the recycling of human bodies reduced to merchandise, ambiguously catering to, and criticizing, the voyeuristic pleasure that devolves from the cinematographic exploitation of bodies.